Cognitive Behavioral Intervention for Youth at Risk for Conduct Problems: Future Directions. Issue 5 (3rd September 2019) - Lochman, John E.; Boxmeyer, Caroline L.; Kassing, Francesca L.; Powell, Nicole P.; Stromeyer, Sara L.
Abstract : This article briefly overviews the history of cognitive behavioral intervention (CBI) for children displaying early signs, or actual diagnoses, of conduct disorders. A series of randomized control trials have identified evidence-based CBI programs for children with these behavior problems at various developmental stages from preschool through adolescence. Although it is critically important for the field to disseminate these existing programs as developed, we argue that it is important to also move beyond the existing evidence-based programs. Research should continue to test new comprehensive, multicomponent interventions, fueled by our evolving understanding of active mechanisms that contribute to children's externalizing behavior problems. The future of research in this area can also benefit from a focus on four central issues. First, research can address how single interventions can have meaningful impact on a range of transdiagnostic outcomes because the intervention mechanisms may affect those various outcomes. Second, rooted in implementation science, we are beginning to understand better how evidence-based programs can be disseminated in the real world, examining key issues such as the adequacy of training approaches and the role of therapist and organizational characteristics. Third, a major focus of research can be on how to optimize intervention outcomes, including a focus on microtrials, on tailoring of interventions, on examining rigorously how interventions are delivered, and on the integration of technology and of other approaches such as mindfulness training into CBI. Fourth, research can explore how the therapeutic relationship and the therapists' characteristics can play substantial roles in effective CBI with conduct problem children.